Oh, that Bubble! - Krishna, Anu (International Journal of Advanced Research in Peace, Harmony and Education; Vol 4 (2019): International Journal of Advance Research in Peace, Harmony and Education, 2019)
We are conditioned to behave in a manner that is highlighted favourably or dusted down unfavourably by the environment and the people in it based on their perceptions and their rule books. No wonder we often chase success at the cost of leaving our loved ones behind and in the end, we feel dissatisfied despite all the adulation, fame and a fat bank balance. Is it maybe time to knock some sense into us and show the way for the future generation to emulate us by unlearning our conditioning and learning that contribution to another person weighs more than achievement for self? If we turn the clock back on simplicity in terms of living in an interconnected world, there would be more happiness to soak in and more happy souls smiling and shining. So, it is time to create that Bubble but how? How to cite this article:  Krishna A.Oh that Bubble. Int J Adv Res Peace Harm Edu 2019; 4: 1-2.